[OP.7A.03] MEASUREMENT OF ARTERIAL AGING IN THE POPULATION. (September 2016) - Hafez, A.; Eber, B.; Weber, T.
Abstract : Objective: The concept of arterial aging and its relationship with arterial stiffness has been successfully introduced. However, the distribution of successful and premature aging in the population is currently unknown. Design and method: We acquired brachial waveforms with automated oscillometric devices (Agedio, i.e.m., Stolberg, Germany) in 13 public pharmacies and at 2 public health events from September to December 2015. Aortic pulse wave velocity (aoPWV) was estimated, using age, systolic blood pressure, and waveform characteristics, with the validated ARCSolver algorithm. Using the 50th and the 90th percentile from a previous population study, we defined age-specific cutoff values for separating arterial age and coded results according to a traffic light system. Results: Overall, we included 1281 persons (33.1% male). Mean age was 59.4 years (SD 15.3, range 20–91). Mean systolic blood pressure was 133 mmHg (SD 17), mean diastolic blood pressure 83 mmHg (SD 12). Hypertension had been diagnosed previously in 38% of participants, and 33% were taking antihypertensive drugs. Diabetes had been diagnosed in 7.2%, and cardiac disease in 11.3%. Mean aoPWV was 8.9 m/sec (SD 2.2, range 4.0–15.2). According to the predefined limits, arterial age was in the green range in 20.4%, in the yellow range in 44%, and in the red range in 35.4%. Participants with hypertension (10.1 vs 8.2 m/sec, p < 0.001), diabetes (9.9 vs 8.8 m/sec, p < 0.001), and cardiac disease (10.5 vs 8.7 m/sec, p < 0.001) had higher aoPWVs, as compared to their counterparts, but age was different between the groups. Distribution of arterial age was different between patients with and without hypertension or cardiac diasease and their counterparts (Table). Conclusions: We provide initial data from a screening approach for arterial aging in the population. The automated and user-independent method we used facilitates screening of large populations. Figure. No caption available.